PENGARUH FAKTOR MOTIVASI KERJA , GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PARA ANGGOTA TENAGA PENDAMPING MASYARAKAT (TPM) DIKABUPATEN CIREBON - Sahlan, Muhammad (JURISMA : Jurnal Riset Bisnis & Manajemen, 2017)
This research is intend to get the empirical evidence of the effect of motivation of work, style of leadership, diciplin of work, to the performance of the accompany volunteers of community (TPM) in Kabupaten Cirebon.The result of this research are expected contibute to improve the management science especially of the human resourches management. For the similar institution and practioners, the research hopely give the usefull information over the motivation of work, style of leadership, dicipline of work, to the performance of the accompany volunteers of community.Survey method and quantitative research used in this research. Path analysis method was used in this research to make the test of check to hypothesis.The result of this research indicated there’s a positive correlation and significantly between the motivation ot work, style of leadership, dicipline of work, toward performance in a manner simultaneously. Whereas in manner partially indicated positively correlation dan significantly between motivation of work to ward performance, style of leadership indecated positively corrlation and significantly toward performance, and dicipline of work indicated positively correlation and significantly toward perfomance. In addition, also in this research come of the fact that motivation of work to form a factor that gives biggest effect if compared to another factor. Keywords : motivation of work, style of leadership, diciplin of work, and performance.